The concept of coexistence in Islamic primary sources an analytical examination - Selim, Ali Shehata Abdou (Cambridge Scholars Publishing, 2015)
The terms `coexistence', `partnership', `citizenship' and `globalization' all have a profound impact on today's decision makers and their policy formation, as well as on individuals